Job Loss, Credit Constraints, and Consumption Growth - Crossley, Thomas F.; Low, Hamish W. (The Review of Economics and Statistics, 2014)
We use direct evidence on credit constraints to study their importance for household consumption growth and for welfare. We distentangle the direct effect on consumption growth of a currently binding credit constraint from the indirect effect of a potentially binding credit constraint that generates consumption risk. Our data are focused on job losers. We find that less than 5% of job losers experience a binding credit constraint, but those who do experience significant welfare losses, and consumption growth is 24% higher than for the rest of the population. However, even among those who are unconstrained and are able to borrow if needed, consumption responds to transitory income.